Effect of the surface topographic modification on cytocompatibility of hardened calcium phosphate cement - Li, Jiyan; He, Fupo; Ye, Jiandong (Applied surface science, 2013)
•The surface of hardened CPC was covered by regular blade-like HA crystals after modified by PEG.•The surface roughness of CPC-P was similar to that of CPC-W.•Ion concentration and pH value of the soaking solution of CPC-P and CPC-W were without significant difference.•Regular blade-like structure was in favor of MC3T3-E1 cells. As cells are inherently sensitive to local nanoscale patterns of topography, the aim of this study was to determine the effect of the topographic modification of hardened calcium phosphate cement on cell response which was conducted with MC3T3-E1 cells. The results exhibited that the samples with regular blade-like crystalline structure had better cell response (cell attachment, viability, proliferation and differentiation) compared to those with irregular blade-like crystalline structure. The method of topographic modification is promising for developing a novel biomaterial of hardened calcium phosphate cement for bone repair.